(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to identify and analyze the effect of price discounts on consumer impulse buying behavior at KIP Store in Bengkulu City. The background of the research is based on the phenomenon of the widespread use of price discounts in modern retail and the increasing tendency of consumers to make spontaneous purchases without prior planning. The research employed a quantitative approach using a survey method, involving 70 respondents selected through probability sampling. Data were collected through questionnaires and analyzed using simple linear regression with the help of SPSS software. The analysis results show that the F-significance value is 0.000 (< 0.05) and the F-calculated value is 33.309, which is greater than the F-table value of 3.978, indicating that price discounts have a significant simultaneous effect on impulse buying. Partially, the price discount variable also has a positive and significant effect, with a significance value of 0.000 (< 0.05) and a t-calculated value of 10.704, which is greater than the t-table value of 1.994. These findings indicate that the more attractive the price discount offered, the higher the tendency of consumers to make impulse purchases.